2021
DOI: 10.1177/0261927x211044799
|View full text |Cite
|
Sign up to set email alerts
|

“We” are in This Pandemic, but “You” can get Through This: The Effects of Pronouns on Likelihood to Stay-at-Home During COVID-19

Abstract: We examine how first-person plural and second-person singular pronouns used in coronavirus disease 2019 (COVID-19) communications impact people's likelihood to follow stay-at-home recommendations. A 2 (first-person plural [“we”] vs. second-person singular [“you”]) by continuous trait self-control between-subjects experiment ( N = 223) was used to examine individuals’ adherence to stay-at-home recommendations. Results suggest that “you”-based appeals may be more broadly effective in garnering stay-at-home adher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…For example, research suggests that the effects of closeness-implying pronouns (“we” versus “you”) used in messaging depend on whether the closeness implied by the pronoun is consistent with how individuals perceive their relationship with the brand ( Sela et al, 2012 ). In other words, if youth do not perceive a close relationship with the brand – such as is likely the case with youth vaping messages – then it is more advisable to use “you” language than “we.” A study exploring pronoun use in terms of health suggestions similarly echoes that “you”-based appeals may be more broadly effective among audiences ( Tu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 93%
“…For example, research suggests that the effects of closeness-implying pronouns (“we” versus “you”) used in messaging depend on whether the closeness implied by the pronoun is consistent with how individuals perceive their relationship with the brand ( Sela et al, 2012 ). In other words, if youth do not perceive a close relationship with the brand – such as is likely the case with youth vaping messages – then it is more advisable to use “you” language than “we.” A study exploring pronoun use in terms of health suggestions similarly echoes that “you”-based appeals may be more broadly effective among audiences ( Tu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 93%
“…Contributing to the sociolinguistics of crisis communication, Ahmad and Hillman ( 2021 ) examined the communication strategies employed by Qatar's government in dealing with the COVID-19 pandemic. While a study by Gallardo-Pauls ( 2021 ) proposed a specifically linguistic/discursive model of risk communication, Tu et al ( 2021 ) inquired into how pronouns “we” and “you” affected the likelihood to stay at home differently. In another study, Tian et al ( 2021 ) investigated the role of pronouns in crafting supportive messages and hope appeals and facilitating people to cope with COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, earlier work on first and second person pronouns in COVID messages (and health messages more generally) is fairly limited, and yields a divergent set of results. In recent work, Tu et al (2021) tested COVID stay-at-home appeals with either you or we, such as "stay home, you can get through this / we can get through this together." They found that messages with second-person you are more effective than ones with firstperson plural we when it comes to shaping people's self-reported likelihood of staying at home vs. going to a friend's party in a hypothetical scenario.…”
Section: Prior Workmentioning
confidence: 99%
“…Kaiser 2021) or the likelihood of different hypothetical or future actions (e.g. Tu et al 2021). These kinds of studies do not provide a measure of incremental, real-time processing and do not provide insights into whether certain linguistic options are harder to process than others.…”
Section: Prior Workmentioning
confidence: 99%